2022
DOI: 10.1177/02698811211055811
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the aryl hydrocarbon receptor by clozapine induces preadipocyte differentiation and contributes to endothelial dysfunction

Abstract: Background: The superior therapeutic benefit of clozapine is often associated with metabolic disruptions as obesity, insulin resistance, tachycardia, higher blood pressure, and even hypertension. Aims: These adverse vascular/ metabolic events under clozapine are similar to those caused by polycyclic aromatic hydrocarbons (PAHs), and clozapine shows structural similarity to well-known ligands of the aryl hydrocarbon receptor (AhR). Therefore, we speculated that the side effects caused by clozapine might rely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Clozapine activates AHR in the cytoplasm and inhibits AMPK signaling, which leads to increased lipid synthesis and metabolic disorders. [55,56]. The Glucocorticoid receptor gene NR3C1 rs6196 is significantly associated with weight gain in patients taking SGAs [57].…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine activates AHR in the cytoplasm and inhibits AMPK signaling, which leads to increased lipid synthesis and metabolic disorders. [55,56]. The Glucocorticoid receptor gene NR3C1 rs6196 is significantly associated with weight gain in patients taking SGAs [57].…”
Section: Discussionmentioning
confidence: 99%
“…AhR plays an important role in adipocyte differentiation, and activation of AhR can significantly promote peroxisome proliferator-activated receptor γ (PPARγ) decay, which was shown to be involved in the mechanism of proteasome-dependent degradation in an in vitro study [ 44 ]. AhR activation induced not only adipogenesis but also vascular endothelial dysfunction in an in vivo model of male mice [ 45 ]. Distel et al [ 46 ] reported that PPARγ agonists could increase lipid turnover and decrease fatty acid release from EAT in an animal model of rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the cytosol, AhR is bound by two heat shock protein 90 (HSP90) chaperones, molecules recently identified as both SCZ and Parkinson's disease (PD) targets [45][46][47][48][49][50][51][52]. Other AhR ligands significant for SCZ include DA, carbidopa, clozapine, melatonin, serotonin, microbial phenazines, and various pollutants, linking endogenous and exogenous molecules to this pathology [53][54][55][56].…”
Section: Dh-discordant Scz Features Non-da Mechanisms Referencesmentioning
confidence: 99%